Fluid surface reconstruction based on specular reflection model. (18th June 2013) - Yu, Mingqi; Quan, Hongyan
ABSTRACT: This paper puts forward a hierarchical method of fluid surface modeling in natural landscapes. The proposed method produces a visually plausible surface geometry with the texture from a single video image recorded by a standard video device. In contrast with the conventional physically based fluid simulation, our method computes preliminary results using empirical method and adopts Stokes wave model to obtain the reconstruction result. We illustrate the working of system with a wide range of possible scene, and a qualitative evaluation of our method is provided to verify the quality of the surface geometry. The experiment shows that the method can meet the requirement of real‐time performance and the reality of the fluid. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : This paper presents a novel calculating process of fluid surface reconstruction. The proposed linear process based on optical theory and fluid physical properties helps designers bypass the ill‐posed problem of shape from shading and provides visual plausible results with a real‐time performance.